Evaluation of Fish Meal Replaced with Leaf Protein Concentrate from Glyricidia in Diets for Broiler - Chicks: Effect on Performance, Muscle Growth, Haematology and Serum Metabolites - Agbede, J.O.; Aletor, V.A. (International Journal of Poultry Science, 2003)
The equi-protein replacement of fishmeal (FM) protein with Glyricidia leaf protein concentrate (GLPC) was evaluated in diets for broiler chicks. Prior to the feeding trial, the GLPC was analyzed for the amino acids and any phytin and tannin contents. Thereafter, five diets were formulated. The control (diet 1) contained 5% FM whose protein was gradually replaced at 25, 50, 75 or 100% with GLPC in diets 2 to 5. Thus the inclusion level of GLPC was 1.81, 3.62, 5.43 or 7.24 respectively for diets 2 to 5. A batch of 300 starter-chicks was randomly assigned in triplicate to these dietary treatments (60 chicks/treatment). The final weight and average weight gain of the chicks fed 1.81% GLPC - based diet was similar (P = 0.05) to those fed the control diet; both being significantly (P = 0.05) higher than those fed 3.62, 5.43 or 7.24% GLPC - based diets. The weight gain, average feed consumption as well as feed efficiency declined as the level of GLPC in the diets increased at the expense of FM protein. Nitrogen retention (NR) of chicks fed 1.81, 3.62 or 5.43% GLPC - based diets was similar to those fed the control diet. At the end of the feeding trial, the chicks were sacrificed for carcass characteristics, relative organ and muscle measurements as well as blood and serum analyses. Relative weights of the heart and belly fat were significantly (P ≤ 0.05) influenced by dietary treatments. Among the muscles weighed, only the relative weight of Pectorialis thoracicus was significantly (P≤0.05) influenced. The weight of P. thoracicus was highest in chicks fed 1.81% GLPC - based diet among the test diets and was similar to those fed the control diet (P = 0.05). Relative lengths of Supra coracoideus and P. thoracicus averaged 17.6 and 20.7 cmkg-1 body weight, respectively while the relative breadth averaged 3.9 and 8.4cmkg-1 body weight, respectively. These values did not vary widely as indicated by the low coefficient of variations. Among the haematological indices, only the Erythrocyte Sedimentation Rate (ESR) significantly (P = 0.05) increased as the level of GLPC increased in the diets while the serum constituents showed no consistent trends related to the dietary treatments. It was concluded that FM protein in the diet for broiler - chicks can be replaced by 25% with GLPC protein without adverse effect on performance, carcass characteristics, muscle development or haematological variables in broiler - chicks.